The Extent of the Practice of Iraqi Banks to Manage Profits Using the (LLp it) Model and Its Reflection on the Tax Base, A Case Study of A Sample of Iraqi Private Banks Listed in The Iraqi Stock Exchange - Nasser, Haider Kathem; Abdullah , Ghaith Arkan; Hammood, Mohammed Hashim (Journal of Economics and Administrative Sciences, 2022)
The research aims to identify the extent to which Iraqi private banks practice profit management motivated by reducing the taxable base by increasing the provision for loan losses by relying on the LLP it model, which consists of a main independent variable (net profit before tax) and independent sub-variables (bank size, total debts to total equity, loans granted to total obligations) under the name of the variables governing the banking business. (Colmgrove-Smirnov) was used to test the normal distribution of data for all banks during the period 2017-2020, and then find the correlation between the main independent variable sub and the dependent variable by means of the correlation coefficient person, and then using the multiple regression model to find the effect between the research variables according to the equation of the LLP it model for a sample of three banks (the Commercial Bank of Iraq, the Bank of Baghdad, the Ashur International Bank) based on a time series extending from (2017-2020). The researchers reached the most important conclusions :The possibility of using the LLP it model on Iraqi banks to reveal the practice of profit management and there is a significant correlation between the net profit before tax and the provision for loan losses. The researchers recommended the most important recommendations: Conducting continuous tests to detect banks that practice earnings management for the purpose of reducing the tax base, the necessity of using modern tools and methods (LLP it) by the tax administration to limit the practice of profit management in order to reduce the tax base